Passively Q-switched and mode-locked zirconia Yttria erbium-doped fiber laser / Raja Zaimas Rosdin Raja Rosdin - Raja Zaimas Rosdin , Raja Rosdin (2023)
Cost-efficient, robust, and stable pulse laser systems are vital for a wide range of applications ranging from optical communication to sensing. This thesis aims to construct practical Q-switched and mode-locked Zirconia-Yttria Erbium-Doped Fiber Laser (Z-EDFL) operating in 1550 nm region using the new saturable absorbers (SAs). Five new SA devices were successfully explored in this work: gold nanoparticles (GNP), silver nanoparticles (SNP), Bismuth tellurite (Bi2Te3), Thulium doped fiber (TDF) and Bismuth-doped fiber (BiDF). For instance, GNP was prepared through sodium borohydrate reduction method and incorporated into an EDFL cavity to generate Q-switched pulses at 1566.7 nm. The Q-switched EDFL produced self-started pulse train with a repetition rate that is tuned from 8.1 to 18.2 kHz as the 980 nm pump power is increased from 83.6 mW to 153.5 mW. At maximum pump power, the laser produced a Q-switching pulse train with the minimum pulse duration and the maximum pulse energyof 25.8 μs and 87.9 nJ, respectively. By adding 200 m long SMF into the same cavity, a mode-locked nanosecond pulses train was also obtained. The nanosecond pulses operate at 1561.5 nm with pulse duration of 202 ns and a fundamental repetition rate of 1.0 MHz. The maximum pulses energy of 199 nJ was observed at 147.2 mW pump power. Dark pulse generation was also successfully achieved by using Bi2Te3 or BiDF based SA in highly nonlinear EDFL cavity with Z-EDF gain medium. For instance, the laser generated a dark pulse with multi-wavelength emission, centered at 1592.68 nm by exploiting the effect of saturable absorption of Bi2Te3 and high nonlinearity of Z-EDF. The laser operated at pulse repetition frequency of 1.0 MHz with a pulse width of 215 ns. These results indicate that the developed SAs have a great potential for fiber laser applications.